I am Pilgrim : a thriller - Hayes, Terry, 1951- (Emily Bestler Books/Atria, a division of Simon & Schuster, Inc., 2014)
"A breakneck race against time ... and an implacable enemy. An anonymous young woman murdered in a run-down hotel, all identifying characteristics dissolved by acid. A father publicly beheaded in the blistering heat of a Saudi Arabian public square. A notorious Syrian biotech expert found eyeless in a Damascus junkyard. Smoldering human remains on a remote mountainside in Afghanistan. A flawless plot to commit an appalling crime against humanity. One path links them all, and only one man can make the journey. Pilgrim."--Publisher's website.